2015
DOI: 10.3892/mco.2015.517
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of osteopontin expression in non-small-cell lung cancer: A meta-analysis

Abstract: Abstract. Osteopontin (OPN) plays an important role in the progression and metastasis of cancer. However, the role of OPN as a prognostic factor in non-small-cell lung cancer (NSCLC) remains controversial. The aim of this study was to investigate the association between OPN expression and prognosis in patients with NSCLC using a meta-analysis. Based on PubMed, Ovid Medline, Embase, ISI, ScienceDirect and SpringerLink databases, related articles published prior to January, 2013 were collected. A meta-analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(27 reference statements)
2
8
0
2
Order By: Relevance
“…In another study, low serum OPN levels were significantly associated with a favorable prognosis in advanced NSCLC (26). Two recent meta-analyses confirmed that OPN seems to be a good prognostic biomarker of the overall survival in NSCLC patients (27,28). These findings are in accordance with the satisfactory prognostic performance of OPN in 1-year survival observed in our study.…”
Section: Serumsupporting
confidence: 91%
“…In another study, low serum OPN levels were significantly associated with a favorable prognosis in advanced NSCLC (26). Two recent meta-analyses confirmed that OPN seems to be a good prognostic biomarker of the overall survival in NSCLC patients (27,28). These findings are in accordance with the satisfactory prognostic performance of OPN in 1-year survival observed in our study.…”
Section: Serumsupporting
confidence: 91%
“…We found several previously published meta-analyses also explored the prognostic significance of OPN in different cancers including breast cancer [ 31 ], colorectal cancer [ 32 ], non-small-cell lung cancer [ 33 ] and glioma [ 34 ]. Xu et al showed that OPN expression was a predictor for poor overall survival and disease-free survival in breast cancer patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…OPN is up-regulated in NSCLC and even more in cells with strong potential and capacity of metastasis and invasion [18,19], which can be attenuated by its deletion [20]. Up-regulation of OPN is proposed to be associated with stages, severities, lymph node metastasis, poor prognosis, and high recurrence [21][22][23]. However, it is still unclear whether OPN is responsible for acquired resistance to EGFR-TKIs.…”
mentioning
confidence: 99%